Clinical study of gestational trophoblastic disease in a tertiary care hospital - Mulik, Jayashree; Choudhary, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Gestational trophoblastic diseases (GTDs) had been associated with significant morbidity and mortality till recently. Wide variation in incidences have been reported worldwide. The present study was planned with the objective of determination of incidence, assessment of risk factors, clinical presentation, management protocols and outcomes in GTD cases in Indian population at a tertiary care centre. Methods: All the diagnosed cases of GTD reporting to study centre during study period of 1.5 years were included. Detailed history taking, examination and relevant investigations (Hb%, blood grouping, thyroid functions, serum ß-hCG, USG and chest X-ray) were undertaken. Suction and evacuation were done for all patients as primary mode of management and samples were sent for histopathological examination. Comprehensive follow ups were done, including weekly ß-hCG until normal for 3 consecutive weeks followed by monthly determination until the levels were normal for 6 consecutive months. Results: Total 22 cases out of 19500 deliveries were diagnosed as GTD (incidence rate-1.13/1000 deliveries). Mean age was 23.64±3.89 years with 50% participants being primigravida. The commonest symptom after amenorrhea 22 (100%) was bleeding per-vaginum 15 (68.2%). Maximum cases were of complete hydatidiform mole histopathology 16 (72.73%), USG 19 (86.4%). Clinical characteristics were statistically comparable between patients of complete mole and partial mole. Out of 22 cases, 1 (4.5%) was diagnosed as GTN. Conclusions: Early diagnosis and treatment along with regular follow up is the key in GTD. There is need to establish a centralized disease specific registry in future.